Investigating Indonesian Novice EFL Teachers’ Manifestations of and Factors Affecting Teaching Anxiety - Adiatmi (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study focuses on Foreign Language Teaching Anxiety among Indonesian novice English as a Foreign Language Teachers, a psychological challenge that affects their confidence and classroom performance. The research aims to explain how anxiety appears during teaching and identify its main causes. Using a qualitative case study approach, the study involved three novice EFL teachers with less than five years of experience in East Java secondary schools. Data were collected through classroom observations and interviews and analyzed using thematic analysis to find patterns in teachers’ experiences. The findings show that anxiety is manifest through behaviors such as pausing or falling silent during lessons, avoidance behaviors, and shifting to safer learning strategies. Physical signs like trembling and fatigue were also observed, which reduce spontaneity and limit students’ exposure to authentic English. Six key factors contribute to teaching anxiety, such as communication apprehension, performance anxiety, fear of negative evaluation, self-perceived language inadequacy, maladaptive beliefs about teaching perfection, and classroom management difficulties. Among these, communication apprehension and classroom management anxiety were the most influential because they directly affect teachers’ willingness to use English in class. The study concludes that teaching anxiety is not only an emotional state but also a factor that shapes teaching strategies and classroom interaction. To reduce anxiety, schools should provide professional development, mentoring, and supportive observation practices to build teacher confidence. Future research should include larger and more diverse samples and use mixed methods to gain deeper insights into this issue.
Reuploud file repositori 22 Mei 2026_Firli Validasi dan Finalisasi Repositori File 11 Juni 2026_Kholif Basri
Keywords: Teaching Anxiety; Indonesian Novice English; Teacher; Anxiety